2022
DOI: 10.1177/1934578x221129106
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Molecular Docking Analysis on Targets and Mechanisms of Berberine in Atypical Antipsychotic-Induced Metabolic Syndrome

Abstract: Berberine (BBR), an isoquinoline alkaloid, possesses multiply pharmacological effects as a potential therapeutic drug for antipsychotic-induced metabolic syndrome (MetS). However, the underlying therapeutic mechanisms have not been fully elucidated. In this study, we aim to investigate the possible mechanisms by identifying the key targets and biological pathways through network pharmacology and molecular docking analysis. A total of 23 overlapping targets in the intersection set among BBR, atypical antipsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The results also showed that berberine has a higher affinity value compared to the native ligand of the PPARG complex (PDB ID:1I7I), with a binding energy value of berberine-PPARG of −8.4 kcal/mol and a binding energy value of ligand-PPARG of −7.6 kcal/mol. These results indicate that berberine compounds have binding potential toward PPARG [57].…”
Section: Berberine As Anti-adipogenic and Anti-hyperlipidemic Agentmentioning
confidence: 59%
“…The results also showed that berberine has a higher affinity value compared to the native ligand of the PPARG complex (PDB ID:1I7I), with a binding energy value of berberine-PPARG of −8.4 kcal/mol and a binding energy value of ligand-PPARG of −7.6 kcal/mol. These results indicate that berberine compounds have binding potential toward PPARG [57].…”
Section: Berberine As Anti-adipogenic and Anti-hyperlipidemic Agentmentioning
confidence: 59%
“…The network analysis conducted has unveiled a complex web of interactions and pathways that illuminate role of berberine in the process of wound healing. Huang et al in their recent publication, reported the network pharmacology-based apprach and identified some key molecualr targets for berberine [47]. Molecular docking study also reported in their work [47].…”
Section: Analysis Of Network Enrichment and Gene Expressionmentioning
confidence: 87%
“…Huang et al in their recent publication, reported the network pharmacology-based apprach and identified some key molecualr targets for berberine [47]. Molecular docking study also reported in their work [47]. Berberine, a naturally occurring isoquinoline alkaloid, has been gaining attention for its potential therapeutic properties, including wound healing.…”
Section: Analysis Of Network Enrichment and Gene Expressionmentioning
confidence: 98%
See 1 more Smart Citation